AN ANALYSIS OF PHATIC EXPRESSION IN INFORMAL COMMUNICATION AT TIME-OUT TALK AMONG RIAU ISLANDS UNIVERSITY (UNRIKA)STUDENTS - Suswanto Ismadi Megah (Universitas Riau Kepulauan, 2016)
This study has objective to analyze phatic expression in informal communication at time-out talk among Riau Islands University students, particularly English department students based on the phatic communication of the theory of Malinowski (1923). The data of this study obtained from the students of Riau Islands University (Unrika), particularly English department students. This tudy used 30 subjects. The data obtained during “time-out talk” to have small talk or during their chatting. The data analyzed qualitatively. The data found of the phatic expression consist of particles, there were 14 data found consist of particles, the word phatic form of the repetition there were 10 data found. The influence of the local language there were 5 data found, and influence of the foreign language there were 11 data found. The study concluded that the usage of the particles of the phatic expression used to make communication to strengthen, to preserve, to maintain the communication, more interesting. Keywords: Phatic expression, informal communication and time-out talk